2014
DOI: 10.1007/s10637-013-0062-5
|View full text |Cite|
|
Sign up to set email alerts
|

Phase I study of PF-04691502, a small-molecule, oral, dual inhibitor of PI3K and mTOR, in patients with advanced cancer

Abstract: Daily oral administration of PF-04691502 was tolerable at 8 mg orally once daily, with a safety profile similar to other PI3K/mTOR inhibitors. PF-04691502 demonstrated PI3K pathway inhibition by changing glucose homeostasis, and by decreasing phosphorylation of downstream molecules in tumor tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 26 publications
2
52
0
3
Order By: Relevance
“…34 In this study, we showed that in primary CLL cells, PF-04691502 induced caspase-dependent apoptosis. In contrast, little effect on the viability of normal B and T lymphocytes was evident.…”
mentioning
confidence: 70%
“…34 In this study, we showed that in primary CLL cells, PF-04691502 induced caspase-dependent apoptosis. In contrast, little effect on the viability of normal B and T lymphocytes was evident.…”
mentioning
confidence: 70%
“…Several dual PI3K/ mTOR inhibitors, such as XL765 (voxtalisib; IC 50 of 157, 39, 113, 9, and 43 nM for mTOR, p110-α, -β, -γ, and -δ, respectively), GDC-0980 (apitolisib; IC 50 of 17, 5, 27, 7, and 4 nM for mTOR, p110-α, -β, -γ, and -δ, respectively), BEZ235 (dactolisib; IC 50 of 6, 4, 5, 7, and 75 nM for mTOR, p110-α, -β, -γ, and -δ, respectively), and PF04691502 (IC 50 of 16, 1.8, 2.1, 1.6, and 1.9 nM for mTOR, p110-α, -β, -γ, and -δ, respectively), are now in clinical development. [63][64][65][66] However, although some objective tumor responses have been observed, the activity of these agents thus far has been modest, and no clinical trial with either a pan-class I PI3K inhibitor or dual PI3K/mTOR inhibitor has reported robust clinical activity, even in tumors with known genetic alterations. 67 Possible reasons for this include (1) uncertainty as to the extent of downstream phosphoprotein biomarker modulation required to result in efficacy in patients; (2) insufficient target inhibition; (3) inappropriate biomarker selection; or (4) inappropriate patient selection.…”
Section: Xl765 (Sanofi) Voxtalisibmentioning
confidence: 99%
“…Furthermore, it is conceivable that continuous inhibition of PI3K/mTOR may result in an adaptation favoring cell growth. 64 For certain conditions harboring driver mutations, such as BCR-ABL in chronic myeloid leukemia, the continued inhibition of kinase activity provided by higher trough concentrations of targeted therapy results in more favorable clinical outcomes. 68,69 However, in other malignancies, models of drug resistance are challenging the requirement for continuous inhibition.…”
Section: Xl765 (Sanofi) Voxtalisibmentioning
confidence: 99%
See 1 more Smart Citation
“…Néanmoins, l'objectif et le plan d'expérience sont rarement détaillés et la taille des cohortes d'expansion est rarement justifiée par une approche statistique rigoureuse, ce qui limite le contrôle du risque d'erreur et la robustesse des conclusions. À titre d'exemple, l'étude publiée par Britten et al n'est pas basée sur des hypothèses statistiques mais sur des considérations pratiques afin d'obtenir un minimum de 5 patients avec une biopsie disponible avant et après le traitement pour l'étude d'un biomarqueur [3]. Penel et al ont proposé une approche pour justifier la taille de ces cohortes à l'aide d'une analyse rétrospective basée sur la probabilité d'observer la TLD à la dose à recommander [4].…”
Section: Introductionunclassified